Impact of Bilingualism on Cognitive Outcome After Stroke. Issue 1 (January 2016) - Alladi, Suvarna; Bak, Thomas H.; Mekala, Shailaja; Rajan, Amulya; Chaudhuri, Jaydip Ray; Mioshi, Eneida; Krovvidi, Rajesh; Surampudi, Bapiraju; Duggirala, Vasanta; Kaul, Subhash
Abstract : Background and Purpose—: Bilingualism has been associated with slower cognitive aging and a later onset of dementia. In this study, we aimed to determine whether bilingualism also influences cognitive outcome after stroke. Methods—: We examined 608 patients with ischemic stroke from a large stroke registry and studied the role of bilingualism in predicting poststroke cognitive impairment in the absence of dementia. Results—: A larger proportion of bilinguals had normal cognition compared with monolinguals (40.5% versus 19.6%; P <0.0001), whereas the reverse was noted in patients with cognitive impairment, including vascular dementia and vascular mild cognitive impairment (monolinguals 77.7% versus bilinguals 49.0%; P <0.0009). There were no differences in the frequency of aphasia (monolinguals 11.8% versus bilinguals 10.5%; P =0.354). Bilingualism was found to be an independent predictor of poststroke cognitive impairment. Conclusions—: Our results suggest that bilingualism leads to a better cognitive outcome after stroke, possibly by enhancing cognitive reserve. Abstract : Supplemental Digital Content is available in the text.